A Declarative Model for Web Accessibility Requirements and its Implementation - Pelzetter, Jens (Frontiers in Computer Science, 2021)
The web has become the primary source of information for many people. Many services are provided on the web. Despite extensive guidelines for the accessibility of web pages, many websites are not accessible, making these websites difficult or impossible to use for people with disabilities. Evaluating the accessibility of web pages can either be done manually, which is a very laborious task, or using automated tools. Unfortunately, the results from different tools are often inconsistent because of the ambiguity of the current guidelines. In this paper, a declarative approach for describing the requirements for accessible web pages is presented. This declarative model will help developers of accessibility evaluation tools to create tools that produce more consistent results and are easier to maintain.